Brain MRI in patients with acute confusional state of diffuse psychiatric/neuropsychological syndromes in systemic lupus erythematosus. Issue 2 (4th March 2017) - Abe, Gakuro; Kikuchi, Hirotoshi; Arinuma, Yoshiyuki; Hirohata, Shunsei
Abstract: Objective : The objective of this study is to explore the characteristics of brain MRI abnormalities in acute confusional state (ACS) in neuropsychiatric systemic lupus erythematosus (NPSLE). Methods : Thirty-six patients with ACS admitted to our institutions from 1992 to 2015 were exhaustively enrolled. Their medical charts and brain MRI scans were reviewed. Results : Eighteen of 36 ACS patients had MRI abnormalities, mostly high-intensity lesions of various sizes in the cerebral white matter. MRI abnormalities improved after treatment in 12 of 14 patients in follow-up studies. MRI abnormalities were not correlated with ages at the onset of ACS, disease durations of SLE, the presence of anti-DNA, anti-phospholipid or anti-ribosomal P antibodies, or IL-6 levels in sera or cerebrospinal fluid. Notably, MRI abnormalities were significantly associated with the presence of serum anti-Sm antibodies ( p  = 0.0067). Finally, eight of the 18 patients with MRI abnormalities, but none of the other 18 patients without MRI abnormalities, died from active SLE. Thus, MRI abnormalities significantly increased the mortality in ACS ( p  = 0.0013, HR =10.36 [95% CI: 2.487–43.19]). Conclusion : These results demonstrate that patients with ACS with MRI abnormalities have more severe diseases, resulting in poorer prognoses. The data also indicate that anti-Sm is involved in the development of MRI abnormalities in ACS.